Challenging established rules for train control through a fault tolerance approach: applications at a classic railway junction. (November 2013) - Liu, Ronghui; Whiteing, Anthony; Koh, Andrew
Current rules of railway operations employed in the UK can be regarded as conservative. While the safety of passengers is a clearly an overriding paramount consideration, such rules may represent a drawback in that they reduce capacity. At present, with high and growing demand there is a clear need to increase railway capacity. While construction of new lines or significant augmentation of existing ones offer ways of providing increased capacity, there is a long gestation period and it is extremely expensive at a time of tight governmental budgetary constraints. A viable alternative is to investigate methods of increasing the productivity of the current infrastructure by understanding how the established rules of railway operation can be challenged without compromising the safety of the passengers. To accomplish this stated goal, a fault-tolerance-based approach to train controls at nodes (junctions and stations) is proposed. This paper introduces the concept of fault tolerance in the context of train operations at a classic railway junction, presents a dynamic, mesoscopic simulation model developed to represent the new control rules and discusses initial results from the application of this approach on capacity gains.